Bryophytes from Nahanni National Park and vicinity, Northwest Territories, Canada. III - Talbot, Stephen S. (Canadian Journal of Botany, 1987)
Forty-four bryophytes are added to the flora of Nahanni National Park and vicinity. Seven species are new to the Northwest Territories.